Direct and indirect effects of perceived social support on women's infertility-related stress - Mariana Martins (2011)
BACKGROUND: Social support can be a critical component of how a woman adjusts to infertility, yet few studies have investigated its impact on infertility-related coping and stress. We examined relationships between social support contexts and infertility stress domains, and tested if they were mediated by infertility-related coping strategies in a sample of infertile women. METHODS: The Multidimensional Scale of Perceived Social Support, the Copenhagen Multi-centre Psychosocial Infertility coping scales and the Fertility Problem Inventory were completed by 252 women seeking treatment. Structural equation modeling analysis was used to test the hypothesized multiple mediation model. RESULTS: The final model revealed negative effects from perceived partner support to relationship concern (beta = -0.47), sexual concern (beta = -0.20) and rejection of childfree lifestyle through meaning-based coping (beta = -0.04). Perceived friend support had a negative effect on social concern through active-confronting coping (beta = -0.04). Finally, besides a direct negative association with social concern (beta = -0.30), perceived family support was indirectly and negatively related with all infertility stress domains (beta from -0.04 to -0.13) through a positive effect of active-avoidance coping. The model explained between 12 and 66% of the variance of outcomes. CONCLUSIONS: Despite being limited by a convenience sampling and cross-sectional design, results highlight the importance of social support contexts in helping women deal with infertility treatment. Health professionals should explore the quality of social networks and encourage seeking positive support from family and partners. Findings suggest it might prove useful for counselors to use coping skills training interventions, by retraining active-avoidance coping into meaning-based and active-confronting strategies.